PENGEMBANGAN SISTEM PAKAR UNTUK DIAGNOSA PENYAKIT TANAMAN HIAS BERBASIS DEMPSTER-SHAFER - Aprianto, Hendri; Sukmana, Rini Nuraini (Infotronik : Jurnal Teknologi Informasi dan Elektronika, 2024)
The advancement of technology has significantly impacted various fields, including agriculture. One application of technology in this sector is the detection of diseases in plants such as cacti, Sansevieria, and succulents. These ornamental plants are popular but susceptible to various diseases that are often difficult to distinguish visually. This research aims to design and develop an expert system for disease detection in cacti, Sansevieria, and succulents using the Dempster-Shafer method. The Dempster-Shafer method is applied in rule formulation, while a relational database model serves as the database structure. The system development follows the prototyping method, with data collected through literature reviews and interviews with domain experts. Testing on Soft Rot disease in cacti demonstrates the system's capability to calculate a certainty level of 0.9075 or 90.75%, indicating the effectiveness of the method in identifying diseases based on observed symptoms. This system is expected to provide significant assistance to farmers and plant enthusiasts in early disease detection, enabling prompt and appropriate treatments to maintain plant health.